Degenerative changes of the corticospinal tract in pediatric patients showing deteriorated motor function: A diffusion tensor tractography study. - Chang, Min Cheol; Jang, Sung Ho; Seo, Jeong Pyo; Lee, Eusil; Kim, Saeyoon; Won, Yu Hui; Son, Su Min (Developmental Neurorehabilitation, 2015)
Objective: We attempted to demonstrate the corresponding degenerative changes of the affected corticospinal tract (CST) in pediatric patients with deteriorated motor function using diffusion tensor tractography (DTT). Methods: We recruited three pediatric patients (corrected age: 2, 6 and 47 months, respectively) who showed impaired motor function. Results: DTT in each patient showed interruption of the CSTs of the hemisphere contralateral to the side of motor impairment. Despite motor impairment and abnormal DTT findings, none of the three patients received rehabilitative therapy. The patients (corrected age: 9, 53 and 59 months, respectively) and their parents visited our clinic again due to deterioration of motor functions. Follow-up DTT of all evaluated patients showed significant degenerative changes in the affected CSTs in accordance with the aggravation of motor impairment. Conclusion: We presented degenerative changes of the affected CSTs in pediatric patients according to the deterioration of motor function.